APPLICATION OF BIOELECTRICAL IMPEDANCE ANALYSIS OF BODY MASS IN ATHLETES - Jasmina Pluncevic Gligoroska; Sanja Manchevska; Lidija Todorovska (College of Sport and Health, Belgrade, 2017)
The primarily role of body mass analysis in sport anthropometry is to determine body mass components, especially muscle component and body fat. The bioelectric impedance analyzes (BIA) employs the principle that the tissues consist of abundance of water and electrolytes, such as muscles, offer less resistance and conduct the current easier than tissue poor with water, such as adipose tissue. The InBody 720 apparatus utilizes the latest technology of measuring body composition using the method of Direct Segmental Multifrequency Bioelectrical Impedance Analysis. InBody’s use four compartments body mass model: the total body water consists of intracellular (ICW) and extracellular water (ECW); the protein compartment, fat free mass (FFM); the mineral compartment and the body fat mass. The aim of this paper is to show which parameters could be obtained by BIA methodology employing the InBody 720 and to make this methodology familiar and recognizable to health and sport practitioners.
PRIMENA METODE BIOELEKTRIČNE IMPEDANSE U ANALIZI TELESNOG SASTAVA SPORTISTA
Keywords: body mass analysis; bioelectrical impedance; athletes